Meningkatkan hasil belajar siswa kelas VI SD Negeri 014 Rambah Hilir pada mata pelajaran IPA dengan metode kooperatif STAD - Suparji (Jurnal Pendidik Indonesia, 2020)
The Natural Science (IPA) subject is one of the curricular study fields in elementary schools. Due to the low understanding of students in the sixth grade of SD Negeri 014 Rambah Hilir, the author conducted a learning improvement study in the first semester of the 2019/2020 academic year. Students had a poor grasp of the learning material and were less active in class, as evidenced by the many low scores in IPA. Therefore, an appropriate instructional improvement using the STAD cooperative learning model was needed. This study aims to improve IPA learning outcomes through the STAD cooperative learning model for sixth-grade students at SD Negeri 014 Rambah Hilir, with a total of 20 students consisting of 12 boys and 8 girls. This research is a classroom action research. The procedure includes planning, action implementation, observation, and reflection. The research instruments were learning tools and data collection tools (test sheets and student observation sheets). The results showed an increase in the class average from 50% in cycle 1 to 70% in cycle 2.